APPLICATION EXPERIENCE OF KEPPRA AND LAMICTAL PREPARATIONS’ COMBINATION IN TREATMENT OF LENNOX-GASTAUT SYNDROME - Stetsyuk, R.А. (World of Medicine and Biology, 2010)
It was examined the effectiveness of Keppra and Lamictal preparations’ combination application to 14 children in treatment of resistant Lennox-Gastaut syndrome. It was proved the clinical effectiveness of the given combination, which manifests in lasting remission of cerebral seizures with correlation on electroencephalogram.
Keywords: Lennox-Gastaut syndrome; polytherapy; remission